PCSK9 Promotes Cardiovascular Diseases: Recent Evidence about Its Association with Platelet Activation-Induced Myocardial Infarction - Meidi Utami Puteri; Nuriza Ulul Azmi; Mitsuyasu Kato; Fadlina Chany Saputri (Life, 2022)
Cardiovascular diseases are the leading cause of death worldwide, with the majority of the cases being heart failure due to myocardial infarction. Research on cardiovascular diseases is currently underway, particularly on atherosclerosis prevention, to reduce the risk of myocardial infarction. Proprotein convertase subtilisin/kexin type 9 (PCSK9) has been reported to play a role in lipid metabolism, by enhancing low-density lipoprotein (LDL) receptor degradation. Therefore, PCSK9 inhibitors have been developed and found to successfully decrease LDL plasma levels. Recent experimental studies have also implicated PCSK9 in platelet activation, having a key role during atherosclerosis progression. Although numerous studies have addressed the role of PCSK9 role in controlling hypercholesterolemia, studies and discussions exploring its involvement in platelet activation are still limited. Hence, here, we address our current understanding of the pathophysiological process involved in atherosclerosis-induced myocardial infarction (MI) through platelet activation and highlight the molecular mechanisms used by PCSK9 in regulating platelet activation. Undoubtedly, a deeper understanding of the relationship between platelet activation and the underlying molecular mechanisms of PCSK9 in the context of MI progression will provide a new strategy for developing drugs that selectively inhibit the most relevant pathways in cardiovascular disease progression.